La novia remisa y el novio ardiente en el epitalamio latino: una imagen que pervive en el Renacimiento - Serrano Cueto, Antonio (Cuadernos de Filología Clásica. Estudios Latinos, 2003)
The author analyses the traditional image of the bridal couple (the unwilling bride, the burning bridegroom) in the humanistic epithalamium in a selection of texts by various poets: Giovanni Pontano, Juan Segundo, Antonio Agustín, Jerónimo Ramírez, Gabriele Altilio, Giovanni Gigli, Manuel da Costa, Callimaco Experiente (Filippo Buonaccorsi) and Martín Ivarra.